Traditional Beers processing in Tanzania: Development Needs - Tiisekwa, Bendantunguka (Afrika Focus, 1986)
A general account of the status of the traditional alcoholic beverages in Tanzania is presented with special focus on sorghum beers. The traditional procedure used to prepare Mtama (sorghum) beer, a popular alcoholic beverage of Tanzania is described. Based on the personal experience of the author himself and on reports in the literature the problem areas requiring technological improvement on this beer are outlined. The case for immediate research needs, aimed at developing a commercially viable Mtama beer, is argued. KEYWORDS : Mtama beer, sorghum beer, Tanzanian beverages traditional alcoholic beverages